Pro Disability Policy in Local Governments: Lessons from the Central Lampung Regency - Hutagalung, Simon Sumanjoyo; Faedlulloh, Dodi (The Center for Disability Studies and Services Brawijaya University, 2021)
All local governments have the same responsibility and obligation in positioning themselves as institution that are friendly to persons with disabilities, including Central Lampung Regency in Lampung Province. There are two important questions from the research which is the basis of this study; (1). What are the efforts made by the Central Lampung Regency government towards groups with disabilities? (2). What are the problems that occur in the management of disability groups in Central Lampung Regency?. The type of this research is descriptive with a qualitative approach. The data used by researchers in this study are sourced from primary and secondary data. In this study, primary data obtained through interview techniques was carried out by giving several questions related to the problem issues in research to the informants who had been determined. Informants in this study was collected with a purposive sampling technique. The key informants in this study were 9 heads of local government organizations, 10 representatives of community organizations, and 5 members of the regional parliament. All of them play a role in data collection activities which include focus group discussions, in-depth interviews, observation, and documentation. Meanwhile, data analysis was carried out using interactive data analysis techniques. In the last three years, the number of people with disabilities in Central Lampung has increased. However, the increase in the number of people with disabilities in Central Lampung is due to the expansion of the meaning and scope of disabilities in Indonesia regulation. It is known that several actions at the level of local government organizations in facilitating groups with disabilities can be designed in a more focused manner in the design of programs and policies covering the government, population and civil registration, social, health, education, employment, and transportation, and public infrastructure sectors.